Consumer Financing Dispute Settlement Patterns During the Covid-19 Pandemic in Wetland Environments - Zakiyah, Zakiyah; Rahmawati, Diana; Mohammad Kasim, Nur; Aulia Rahmady, Muhammad; Azhari Rahman, Muhammad (International Journal of Law, Environment, and Natural Resources, 2022)
The pandemic Covid it had an impact on all economic sectors which had an impact on the smooth running of consumers in paying consumer financing installments, which led to consumer financing disputes. The people of South Kalimantan who live in a wetland environment have local wisdom in resolving disputes with Adat Badamai tradition. This study aims to find patterns of dispute resolution between consumers and finance companies during the covid 19 pandemic and to analyze whether local wisdom in the wetland environment, namely the Bahamian custom is reflected in the settlement of consumer financing disputes. The research method used is empirical legal research supported by library research. (library research), is prescriptive analytics, it is hoped that a comprehensive, in-depth and systematic picture will be obtained. This research was conducted in South Kalimantan Province. The results showed (1). consumer financing dispute settlement patterns prioritize settlements outside the court (non-litigation), namely by internal company settlements; use third party services; through the Consumer Dispute Resolution Body, if an amicable agreement is not reached, as a last resort, a court settlement (litigation) is taken. (2). Dispute Resolution Financing companies in South Kalimantan have implemented the customary value of Adat Badamai in the settlement of consumer financing disputes. In the Banjar community, if there is a dispute, they tend to choose to settle it peacefully, meaning that there is no need for the settlement to go to court. Adat Badamai tradition is quite effective and plays a role in creating security and peace among the disputing community members.